藿香 및 廣藿香의 위장관 효능에 대한 실험연구 고찰 - 정의민(Ui Min Jerng); 오용택(Yong Taek Oh); 김정훈(Jung Hoon Kim) (동의생리병리학회지, 2017)
The pharmacological rationale of Agastache rugosa (AR) or Pogostemon cablin (PC), which have been used in traditional Korean medicine to treat dampness pattern or syndrome in gastrointestinal tract, was investigated on the gastrointestinal disorders. In-vivo model studies that examined the effect on the gastrointestinal disorders of AR or PC were collected. They were classified into disease-induced in-vivo models or non-disease in vivo models. The target disease, animal species, induction method, administration, and outcomes (changes in morphological and histological parameter, or blood and fluid) of each study were analyzed. The therapeutic mechanism of AR or PC extract was evaluated by the induced diseases and the changes in outcomes. There were contradictory reports on gastrointestinal motility of AR or PC in disease non-disease in-vivo model. AR or PC inhibited gastrointestinal motility in disease model of increased gastrointestinal motility, while promoted motility in disease model of decreased gastrointestinal motility. AR or PC also inhibited inflammatory changes in gastrointestinal inflammation model. These results suggest that the bidirectional regulation of gastrointestinal motility and the improvement of gastrointestinal inflammatory disorders might underpin traditional therapeutic effect of AR or PC, that is effect to resolve dampness of gastrointestinal tract. KCI Citation Count: 0